Boletim Atlas ODS Amazonas V.2 N.12 - Especial COVID-19 - Pereira, Henrique dos Santos (Brasil, 2020)
Studies on the spread and progression of pandemics from infectious respiratory diseases point to a recurrent pattern characterized by a hierarchical spread combined with small-scale wave behavior and long-range propagation events synchronizing distant populations. One of the challenges of crisis management is to detect the peak moment and the duration of the wave or successive waves that can safely indicate the relaxation of preventive measures or readiness.